2006
DOI: 10.4141/p06-043
|View full text |Cite
|
Sign up to set email alerts
|

Seeding date, row spacing, and weed effects on soybean isoflavone concentrations and other seed characteristics

Abstract: 20-, 40-and 60-cm) and weeds (presence or absence) on soybean isoflavone concentrations and isoflavone yield. Total and individual isoflavone concentrations were determined by HPLC. Seed yield, and oil and crude protein (CP) concentrations were concurrently determined. Year, seeding date, and weeds affected total and individual isoflavone concentrations, while row spacing had no effect. Total isoflavone concentration was 84% greater in 2003 than 2004. Seeding in mid-June increased isoflavone concentration by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
2
26
2
Order By: Relevance
“…Although the environment and G )E interaction were reported as significant factors for isoflavone content, the means comparison found that differences in isoflavone content were significant between the classes. The findings that isoflavone content and protein content are negatively correlated are consistent with the results of other studies (Chiari et al 2004;Seguin et al 2004;Primomo et al 2005;Al-Tawaha and Seguin 2006). Although the relationship between isoflavone and protein was negative, genotypes were identified, such as entry 8 in Group A and entries 13 and 15 in Group B that had high isoflavone content (approximately 3500 mg g (1 ) and moderate protein levels (42%).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Although the environment and G )E interaction were reported as significant factors for isoflavone content, the means comparison found that differences in isoflavone content were significant between the classes. The findings that isoflavone content and protein content are negatively correlated are consistent with the results of other studies (Chiari et al 2004;Seguin et al 2004;Primomo et al 2005;Al-Tawaha and Seguin 2006). Although the relationship between isoflavone and protein was negative, genotypes were identified, such as entry 8 in Group A and entries 13 and 15 in Group B that had high isoflavone content (approximately 3500 mg g (1 ) and moderate protein levels (42%).…”
Section: Resultssupporting
confidence: 81%
“…Positive associations (Primomo et al 2005;Seguin et al 2004;Wang et al 2000;Yin and Vyn 2005), negative associations (AlTawaha and Seguin 2006) and no associations (Charron et al 2005) have been reported between total isoflavone concentration and seed yield. Wang et al (2000) observed differences in total isoflavone concentration among maturity groups; however, a significant correlation between total isoflavone content and days to maturity was not found.…”
mentioning
confidence: 99%
“…2004, Al‐Tawaha et al. 2006, Al‐Tawaha and Seguin 2006). Of all these factors, irrigation has resulted in some of the greatest isoflavone concentration increases reported in field studies.…”
Section: Introductionmentioning
confidence: 99%
“…These effects have been attributed to a large extent to the phytochemicals called isoflavones, which occur naturally in soybean seeds and soy products. Recent studies have uncovered substantial differences in isoflavone levels among Canadian soybean varieties (Primomo et al 2005a;Al-Tawaha and Seguin 2006).…”
Section: Increasing Nutraceuticals In Seedmentioning
confidence: 99%